Aspek Psikologis dan Nilai Moral Tokoh Utama dalam Novel Tuan Ken(tut) Karya FX Rudy Gunawan - Yulianti, Erika; Arifin, Zaenal; Sumadyo, Bambang (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2024)
This research aims to describe the psychological condition and moral values of the main character in the novel, namely a man named Ken Turangga Abdi Nuswantoro, with pressure from both internal and external aspects of the family, school, and society as well as various moods that influence him and individual, social and religious morals in the novel Tuan Ken(tut) by FX Rudy Gunawan. The research method used to analyze this novel is using a qualitative descriptive analysis method with content analysis through quotes from character scenes in the novel. Apart from that, the author uses a psychological approach in preparing work steps. After the author analyzed the novel Tuan Ken(tut) through analysis of psychological aspects, the results found id (the thing that underlies a person's personality, namely consciousness) 2 quotes (2.6%) with ego findings (the will that arises from a person, namely preconscious) 4 quotes (5.7%), super ego (determining the value of right and wrong in everything) 4 quotes (9.4%), eros (things that push towards positivity) 2 quotes (6%), and thanatos (pushing towards negative things, namely damage to death) 8 quotes (23.55%). Moral values, the results obtained are the discovery of elements of individual moral values (rules that regulate the definition of good or bad human actions between the hopes and goals of human life) 1 quote (1.4%), social moral values(actions that have a direct impact on the lives of people fellow humans) 12 quotes (57.6%), and religious moral values (human attitudes regarding obedience to God's commands and remembering God directly) 2 quotes (3.87%).